Action-based quality management : strategy and tools for continuous improvement - Alvarez-Garcia, Jose; Peris-Ortiz, Marta (Springer International Publishing, 2014)
Featuring case studies from the industrial and tourism sectors, this book provides an interdisciplinary perspective on the effect of total quality management on business and innovation strategies. The principles of Total Quality Management (TQM) have been widely researched and analyzed as an essential tool for businesses to compete in a globalized economy. This book presents the latest research on the applications of TQM across different functions such as customer service, human resources management, and cost control. It demonstrates how the utilization of TQM tools, such as the SERVQUAL model, Eco-Management and Audit Scheme (EMAS), High Involvement Practices (HIWP), and the EFQM excellence model, impacts a firm's performance, enhances productivity and innovation, and reduces cost, thereby allowing them to compete more effectively in the global market. Building on the extensive literature on the relationship between TQM and business performance, the authors argue that quality acts as a powerful competitive tool that companies should embrace in their corporate strategy. By promoting activities that result in greater efficiency, improved control and management of the organization (internal quality), firms can achieve significant improvement in customer satisfaction, employee satisfaction, social impact and business results (external quality) and exceed expectations in these areas.